Islamic Banking Regulations in Light of Basel II - M. Kabir Hassan (International Institute of Islamic Thought, 2010)
This paper seeks to determine whether the existing regulatory standards and supervisory framework are adequate to ensure the viability, strength, and continued expansion of Islamic financial institutions. The reemergence of Islamic banking and the attention given to it by regulators around the globe as to the implications of a recently issued Basel II banking regulation makes this article timely. The Basel II framework, which is based on minimum capital requirements, a supervisory review process, and the effective use of market discipline, aligns capital adequacy with banking risks and provides an incentive for financial institutions to enhance risk management and their system of internal controls. Like conventional banks, Islamic banks operate under different regulatory regimes. The still diverse views held by the regulatory agencies of different countries on Islamic banking and finance operations make it harder to assess the overall performance of international Islamic banks. In light of the increased financial innovation and diversity of instruments offered in Islamic finance, the need to improve the transparency of bank operations is particularly relevant for Islamic banks. While product diversity is important in maintaining their competitiveness, it also requires increased transparency and disclosure to improve the understanding of markets and regulatory agencies. The governance of Islamic banks is made even more complex by the need for these banks to meet a set of ethical and financial standards defined by the Shari`ah and the nature of the financial contracts banks use to mobilize deposits. Effective transparency in this area will greatly enhance their credibility and reinforce their depositors and investors’ level of confidence.